The impact evaluation of thermal Al-Musayyib electric power station waste in soil and plant pollution in some heavy metals - AL-Wotaify, Abbas Sebur Serwan; Al-Msafree, Marwa Ahmed Saeed (Journal of Kerbala for Agricultural Sciences, 2018)
The research included study of soil heavy metals content on effect of the Electricity Almusayab Thermal Station and comparative soil of Alexandria city in Babylon Governorate between the longitude °32 77' 811'' N and the latitudes °44 29' 00'' E. In contamination soil was content of Ti: 1.00 to 9.84.00, Co: 20.40-42.00, As: 10.20-12.20, Se: 0.50 and Zn: 150.50-612.00mg kg-1. While in comparative soil was content of these heavy minerals: 7.96, 17.10, 11.70, 0.50 and 155.50 mg kg-1 respectively. These resulted in an increase of 377.70-739.00 mg kg-1 for Ti in the dry matter of the leaves and roots of the rest crop in the affected soils by the residues and between 282.30-343.30mg kg-1 in comparative soil. While Co was 3.90mg kg-1 in dry matter content for both affected and unaffected soil, so As was 0.20-1.40 and 0.10-0.70mg kg-1, as well as Se and Zi were 0.50 0.70-5.10 and 1.40 mg kg-1 respectively in the dry matter at the soil affected by wastes and the Comparative soils. Through soil content of the heavy metals under study, the enrichment factor in affected soil by the residues for Ti was 0.01-12.21, Co: 0.18-2.19 , As: 0.86-1.01, Se:0.88-1.06 , and within the minimum metal level. While the enrichment factor in the dry matter of the leaves of the leaves and roots was 1.10-2.62 for Ti, Co: 1.00, As, Se and Zi were 2.00, 1.00, and 0.50-3.64 respectively. The contamination factor of Ti was 0.01 to 1.24, Co: 1.9-2.46, As: 0.87-1.04, Se: 1.00 and Zi:0.97-3.94 in the affected soil by the residues, which is at a moderate level. In the vegetative parts it was 411.10-2.62, 1.00, 2.00, 1.00, and 50.50-4.64 for those metals respectively. The plant concentration factor of metals in leaves was 38.58 for Ti, Co: 0.12, As: 0.02, Se: 1.00 and Zi: 0.00. And it was 75.49, 0.12, 0.11, 1.00 and 0.03 respectively in the dry matter for the roots of the grown leguminous plant on study soils.